IMPLEMENTASI KEBIJAKAN WALIKOTA BINJAI DALAM MEMBERIKAN BANTUAN SOSIAL KEPADA MASYARAKAT PADA SAAT PANDEMI COVID-19 DI KOTA BINJAI (Studi Perspektif Tentang Peraturan Walikota Dalam Pemberian Bantuan Sosial) - Firmansyah Putra Surbakti; Marzuki Marzuki; Mukidi Mukidi (Jurnal Ilmiah METADATA, 2021)
Social assistance is the provision of assistance that is not continuous and selective in the form of money / goods to the community with the aim of improving the welfare of the community. The formulation of the problem in this thesis is how the Binjai Mayor's policy implementation in providing social assistance, the human resource capacity of the Social Service in distributing social assistance, procedures and mechanisms for distributing social assistance. This type of research is a normative juridical research which is based on statute and empirical juridical research by conducting interviews with staff / employees of the Binjai Social Service. The data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. The conclusion in this paper is carried out using deductive-inductive thinking logic, which is done with the theory used as a starting point for conducting research. The results showed that the implementation of the Binjai Mayor's policy in providing social assistance is that social assistance can be given to individuals or families that cannot be planned in advance and in providing social assistance, the Regional Government still pays attention to regional financial capabilities. The ability of the Social Service's human resources in distributing social assistance is a committee formed to collect data and distribute social assistance to underprivileged residents affected by Covid-19 in Binjai City, which is tasked with coordinating the planning of distributing social assistance to less fortunate people affected by Covid-19 in Binjai City The procedures and mechanisms for distributing social assistance are that potential recipients are people who are included in the RT / RW data collection and are in Kelurahan / Desa, have lost their livelihoods in the midst of the corona pandemic, prospective recipients are not registered as other recipients of social assistance from the central government.